2017
DOI: 10.20448/2003.11.11.15
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Guidance and Counselling in Effective Teaching and Learning in Schools: The Cameroonian Perspective

Abstract: The total development of a child can only take place in an environment conducive for teaching and learning. It is in realization of the above that all educational services which can promote teaching and learning in schools are given prominent attention by educational planners. Counselling services are among the school educational services. It is believed that guidance and counselling services in school shall develop, assess and improve educational programmes; enhance teaching and improve the competence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 1 publication
(1 reference statement)
4
25
0
1
Order By: Relevance
“…21 Furthermore, regarding interpersonal relationship characteristics of nursing clinical educators, it was noticed that the participants provide positive perception. This finding in accordance with Moses (2017) who stated that knowledge and skill transition, which is at the focus education, based deeply on the interpersonal success of the educator. His/her interaction and communication successfully with patients, staff, and students is an important factor of his/her success.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…21 Furthermore, regarding interpersonal relationship characteristics of nursing clinical educators, it was noticed that the participants provide positive perception. This finding in accordance with Moses (2017) who stated that knowledge and skill transition, which is at the focus education, based deeply on the interpersonal success of the educator. His/her interaction and communication successfully with patients, staff, and students is an important factor of his/her success.…”
Section: Discussionsupporting
confidence: 90%
“…He/ she struggles to continue her authenticity as individual and as a professional nurse. 22 Also, the study participants reported positive perception about their clinical educators in relation to evaluation of students. This finding in the line with Yeom (2016) who mentioned that evaluation of performance is also an significant part of the educator's role therefore educators support students to make the associations between theory and practice.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, from the two samples above (2) and 3, it can be identified that the indicator of restrictive appositive is the existence of the same unit of meaning which cannot be separated each other. In other words, the appositive becomes the definer of the anchor.…”
Section: Restrictive Appositive Vs Nonrestrictive Appositivementioning
confidence: 99%
“…The Guidance and Counseling service program in Senior High School is a process of providing assistance to students both individually and in groups in to achieve optimal levels of development and independence (Nkechi et al, 2018), based on the norms prevailing in the society. ( GC for the Guidance and Counseling).…”
Section: Introductionmentioning
confidence: 99%